PENINGKATAN HASILBELAJAR SISWA DALAM PEMBELAJARAN PKn MODEL TIPE STAD DI KELAS IV SEKOLAH DASAR - Purnawati, Purnawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research to remark the lessons process to produce learning in civics (PKn) in class. So it can increase the lesson process in class IV in SD Negeri 13 Kubu Anau kec. Lubuk Basung Kab Agam. This research used the lesson model Cooperative Type Student Teams Archievement Divisions (STAD) is to the student centered its can look in student mark . The Value that they get in siclus I 68 % and increased in siclus II 84 %.